Tindak Tutur Ekspresif dalam Film Raya and the Last Dragon - Chicenia Aprilianisa (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study aims to describe the types of expressive speech acts uttered by the character Raya in the film Raya and the Last Dragon. This study applied a pragmatic approach, focusing on speech act theory and context to understand the meaning of the utterances made by the character in various communicative situations. The method used is a descriptive qualitative method. The research data consists of Raya’s utterances containing expressive speech acts in the film Raya and the Last Dragon. Data collection was conducted through observation and note-taking while data analysis involved identifying, classifying, and describing the utterances based on the type of expressive speech act and the underlying context. The results of the study indicate that there are eleven types of expressive speech acts used by the character of Raya, namely gratitude, admiration, enthusiasm, surprise, worry, disappointment, anger, panic, apology, hope, and regret. Raya uses these expressive speech acts to convey various psychological states that arise in response to events, conflicts, and interactions with other characters